Pembinaan Guru dengan Pendekatan Supervisi Direktif - Yulianto, Edi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
Teacher development is an important aspect in the development of professionalism and quality of education. The directive supervision approach has become an interesting topic in this context, in which the supervisor acts as a leader who provides directions and instructions to the teachers being coached. The purpose of this study is to explore a deeper understanding of the directive supervision approach in teacher development and its impact on improving the quality of teaching. This study uses the literature review method by exploring and processing existing writings and literature but which are in line with the focus of the problem under study. The results of the study show that the directive supervision approach is effective in developing teachers. By providing clear directions and instructions, supervisors can help teachers understand appropriate teaching expectations and provide feedback directly related to their performance. This research provides a better understanding of the importance of teacher development with a directive supervision approach. The results can be used as a guide for supervisors and policy makers in developing effective teacher development programs.